Ketidakpatuhan Tiongkok terhadap Sino-British Joint Declaration dalam Implementasi Kebijakan “One Country, Two Systems” Hong Kong - Putri, Cindy Claudia (Universitas Jember, 2023)
In general, this research discusses China's non-compliance with the Sino-British Joint Declaration agreement in implementing policies on the principle of